Quantifying the influence of dispersion interactions on the elastic properties of energetic NTO polymorphs - Jin-ning Hu; Xiao-jing Fan; Jun-feng Wang; Shao-hua Jin; Chang-jun Zhao; Xiu-tian-feng E; Chao-yang Zhang; Liang-liang Niu (Energetic Materials Frontiers, 2025)
3-Nitro-1,2,4-triazole-5-one (NTO) is a promising energetic compound with high energy and low sensitivity. Herein, the elastic properties of three NTO polymorphs are studied using dispersion-corrected density functional theory. The calculation results of three NTO crystal forms show that C11 is 47–64 GPa, and C22 and C33 are 15.8–19 GPa. We show that more than half of the isotropic elasticity of NTO polymorphs arises from the contribution of London dispersion interaction, which is generally considered to be a weak term. Among the polymorphs, β-NTO is demonstrated to be the stiffest and most anisotropic due to the strongest intermolecular electrostatic interactions and hydrogen bonds. Interestingly, the quantification of elasticity anisotropy demonstrates that the London dispersion interactions also contribute to the anisotropy of energetic molecular crystals. These findings facilitate our fundamental understanding of the elastic properties and the structure-property relationships of energetic polymorphs.